Effect of selective serotonin reuptake inhibitor on prefrontal-striatal connectivity is dependent on the level of TNF-α in patients with major depressive disorder. Issue 15 (6th December 2018) - Liu, Kai; Zhao, Xiaohua; Lu, Xiaobing; Zhu, Xiaoxia; Chen, Hui; Wang, Mengmeng; Yan, Weixin; Jing, Linlin; Deng, Yanjia; Yu, Lin; Wu, Huawang; Wen, Ge; et al.
Abstract: Background: We hypothesize that the tumor necrosis factor-α (TNF-α) may play a role in disturbing the effect of selective serotonin reuptake inhibitor (SSRI) on the striatal connectivity in patients with major depressive disorder (MDD). Methods: We performed a longitudinal observation by combining resting-state functional magnetic resonance imaging (rs-fMRI) and biochemical analyses to identify the abnormal striatal connectivity in MDD patients, and to evaluate the effect of TNF-α level on these abnormal connectivities during SSRI treatment. Eighty-five rs-fMRI scans were collected from 25 MDD patients and 35 healthy controls, and the scans were repeated for all the patients before and after a 6-week SSRI treatment. Whole-brain voxel-wise functional connectivity (FC) was calculated by correlating the rs-fMRI time courses between each voxel and the striatal seeds (i.e. spherical regions placed at the striatums). The level of TNF-α in serum was evaluated by Milliplex assay. Factorial analysis was performed to assess the interaction effects of 'TNF-α × treatment' in the regions with between-group FC difference. Results: Compared with controls, MDD patients showed significantly higher striatal FC in the medial prefrontal cortex (MPFC) and bilateral middle/superior temporal cortices before SSRI treatment ( p < 0.001, uncorrected). Moreover, a significant interaction effect of 'TNF-α × treatment' was found in MPFC-striatum FC in MDD patients ( p = 0.002), and the significance remained after adjusted for age, gender, head motion, and episode of disease. Conclusion: These findings provide evidence that treatment-related brain connectivity change is dependent on the TNF-α level in MDD patients, and the MPFC-striatum connectivities possibly serve as an important target in the brain.